Growing up with idiopathic short stature: psychosocial development and hormone treatment; a critical review - Balen, H Visser‐van (BMJ Group, 2006)
To facilitate decisions on interventions in medically referred children with idiopathic short stature, the research on psychosocial functioning of these children, possible risk and protective factors influencing adaptation, and effects of hormone treatment were reviewed. Parents ranked the behaviour of their children on average between normal and below normal. The magnitude of these deviations varied from small to large. Little is known about the children's self‐perceived psychosocial functioning. Some risk factors were found: being teased, being juvenilised, being a boy, having a younger but taller sibling, low intelligence, and low socioeconomic status. There have been few studies on the impact of protective factors including temperament, coping strategies, and social support. On average, hormone treatment did not improve psychosocial functioning. The research shows the advantages and disadvantages of hormone treatment that must be considered when choosing a suitable intervention. It is suggested that psychosocial adjustment can be improved by focusing on factors other than height alone.